Ultrasonographic Guidance and Characterization of Cryoanalgesic Lesions in Treating a Case of Refractory Sural Neuroma - Ellen E. Rhame; Alexander F. DeBonet; Thomas T. Simopoulos (Case Reports in Anesthesiology)
The recurrent pain of a neuroma following surgical excision and burial of nerve endings can be clinically challenging to manage. Cryoanalgesia in conjunction with ultrasound guidance was used successfully to manage this type of pain. Furthermore, ultrasound provided visualization of the cryolesions, as well as the relationships of the ice ball to the surrounding tissue. Following the completion of the freeze cycle, the tissue can be monitored for return to its usual morphology during the thaw period.